Immediate and fixed implant-prosthetic rehabilitation of the completely edentulous jaws: the “Roman Bridge Protocol”. - Gallottini, S.G.; Gallottini, L.; Ingletto, R. (Journal of Osseointegration, 2024)
Aim The aim of this study was to describe a new technique for implant-prosthetic rehabilitation of the edentulous jaws, based on both scientific evidences and our own clinical records, named “Roman Bridge Protocol”. Completely edentulous jaws is a very critical condition that requires an urgent solution in order to satisfy multiple expectations and needs from patients. Standard removable prosthesis does not represent a valid approach since this solution is not able to gratify both clinician and patients. Nowadays, there are several implant-prosthetic options, such as the “All-on-4” technique, which can restore a good aesthetic and efficient dental arch by the use of total fixed prosthesis anchored to dental implants. Total, fixed and immediate rehabilitation represents a very interesting alternative approach. Materials and methods Our technique consists of an implant- prosthetic rehabilitation of completely edentulous jaws or future completely edentulous jaws. In this second case, it is necessary to proceed with multiple teeth and immediate post-extraction implants that have to be positioned. The surgical procedure considers the use of only four loaded implants, based on the “All-on-4” surgical protocol, of which two distals and two mesials. The implant- prosthetic approach, instead, will use an immediate function Toronto Bridge application within 24 hrs. Our study described an improved and integrated implant-prosthetic technique based on the “All-on-4” concept. Our diagnostic, surgical and prosthetic protocol further ameliorate this procedure, in order to make it more reproducible in everyday dental practice, obtaining excellent and reproducible results. Results Total, fixed and immediate implant-prosthetic rehabilitation of completely edentulous jaws based on the “Roman Bridge Protocol” is a valid therapeutic alternative that can efficiently meet particular needs and expectations from patients.